Chronic hepatitis B virus infection drives changes in systemic immune activation profile in patients coinfected with Plasmodium vivax malaria. - Luís A B Cruz; Marina O A Moraes; Matheus R Queiroga-Barros; Kiyoshi F Fukutani; Manoel Barral-Netto; Bruno B Andrade (Public Library of Science (PLoS), 2019)
Background Plasmodium vivax and Hepatitis B virus (HBV) are globally outspread in similar geographic regions. The concurrence of both infections and its association with some degree of protection against symptomatic and/or severe vivax malaria has been already described. Nevertheless, data on how host response to both pathogens undermines the natural progression of the malarial infection are scarce. Here, a large cohort of vivax malaria and HBV patients is retrospectively analyzed in an attempt to depict how inflammatory characteristics could be potentially related to the protection to severe malaria in coinfection. Methods A retrospective analysis of a databank containing 601 individuals from the Brazilian Amazon, including 179 symptomatic P. vivax monoinfected patients, 145 individuals with asymptomatic P. vivax monoinfection, 28 P. vivax-HBV coinfected patients, 29 HBV monoinfected subjects and 165 healthy controls, was performed. Data on plasma levels of multiple chemokines, cytokines, acute phase proteins, hepatic enzymes, bilirubin and creatinine were analyzed to describe and compare biochemical profiles associated to each type of infection. Results Coinfected individuals predominantly presented asymptomatic malaria, referred increased number of previous malaria episodes than symptomatic vivax-monoinfected patients, and were predominantly younger than asymptomatic vivax-monoinfected individuals. Coinfection was hallmarked by substantially elevated concentrations of interleukin (IL)-10 and heightened levels of C-C motif chemokine ligand (CCL)2. Correlation matrices showed that coinfected individuals presented a distinct biomarker profile when compared to asymptomatic or symptomatic P. vivax patients, or HBV-monoinfected individuals. Parasitemia could distinguish coinfected from symptomatic or asymptomatic P. vivax-monoinfected patients. HBV viremia was associated to distinct inflammatory profiles in HBV-monoinfected and coinfected patients. Conclusion The findings demonstrate a distinct inflammatory profile in coinfected patients, with characteristics associated with immune responses to both pathogens. These host responses to P. vivax and HBV, in conjunction, could be potentially associated, if not mainly responsible, for the protection against symptomatic vivax malaria.